2006
DOI: 10.1016/j.bbapap.2006.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability landscape for Klenow DNA polymerase as a function of pH and salt concentration

Abstract: The thermal denaturation of Klenow DNA polymerase has been characterized over a wide variety of solution conditions to obtain a relative stability landscape for the protein. Measurements were conducted utilizing a miniaturized fluorescence assay that measures Tm based on the increase in the fluorescence of 1,8-anilinonaphthalene sulfonate (ANS) when the protein denatures. The melting temperature (Tm) for Klenow increases as the salt concentration is increased and as the pH is decreased. Klenow's Tm spans a ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…There is a body of work which studies the role salts play during the unfolding of proteins induced by urea, guanidinium HCl, low pH, and heat . The role of salts during heat‐induced unfolding is not clear from the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a body of work which studies the role salts play during the unfolding of proteins induced by urea, guanidinium HCl, low pH, and heat . The role of salts during heat‐induced unfolding is not clear from the literature.…”
Section: Introductionmentioning
confidence: 99%
“…There is a body of work which studies the role salts play during the unfolding of proteins induced by urea, [11][12][13] guanidinium HCl, 14 low pH, 15,16 and heat. [17][18][19][20][21][22] The role of salts during heat-induced unfolding is not clear from the literature. Research on the effect of the anions on unfolding of the B1 domain of protein L demonstrated that sulfate, phosphate and fluoride stabilized, while chloride was neutral and nitrate, perchlorate and thiocyanide destabilized the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental measurements and theoretical results have shown that subtle and small changes in salt concentration can have a strong effect on a broad spectrum of protein properties. For instance, the stability of proteins as well the protein's association with molecules ranging from small charged peptides and drugs to larger proteins and polysaccharides at both the kinetic and thermodynamic level, can be altered by changing the salt type and concentration 16. We still lack a complete theoretical understanding of why increasing the salt concentration and changing the salt type can either enhance or diminish protein stability and binding to charged ligands ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It can also identify other conditions (such as variations in buffer, pH, salt and glycerol concentration, types of cations, etc.) that stabilize proteins and thus make them more amenable to purification and crystallization 1215. It is applicable to a wide variety of eukaryotic and prokaryotic proteins and yields results comparable to static light scattering (SLS) measurements of protein aggregation 4,11,16…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of factors affecting proteins' melting curves have focused almost exclusively on identifying factors that increase T m 1215. However, in setting up a thermal melt-based high-throughput screen (HTS) designed to identify inhibitors or other ligands of a particular protein, the absolute value of the T m is less important than the variability of T m measurements.…”
Section: Introductionmentioning
confidence: 99%